Володимир та Розалія Винниченки: родинне листування (1921 – 1949 роки) - Миронець, Н. (Слово і Час, 2015)
У статті розглядається взаємне листування Володимира Винниченка із дружиною Розалією Винниченко за 1921–1949 рр., яке зберігається в Архіві імені Д. Антоновича УВАН (США). The paper analyzes the family correspondence between Volodymyr Vynnychenko and his wife Rosaliya Vynnychenko which came about during 1921–1949 and is kept in D. Antonovych archive in UVAN – Ukrainian Academy of Arts and Sciences in the U.S.